2012
DOI: 10.3390/s120201720
|View full text |Cite
|
Sign up to set email alerts
|

Signal Processing of MEMS Gyroscope Arrays to Improve Accuracy Using a 1st Order Markov for Rate Signal Modeling

Abstract: This paper presents a signal processing technique to improve angular rate accuracy of the gyroscope by combining the outputs of an array of MEMS gyroscope. A mathematical model for the accuracy improvement was described and a Kalman filter (KF) was designed to obtain optimal rate estimates. Especially, the rate signal was modeled by a first-order Markov process instead of a random walk to improve overall performance. The accuracy of the combined rate signal and affecting factors were analyzed using a steady-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…And the detailed results are illustrated in Table 3. The simple average and the Kalman filter in [8,9,11] are competitors. In this paper, the accuracy means the closeness between the results of measurement and the true angular rate, which can be represented by the amount of measurements errors.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…And the detailed results are illustrated in Table 3. The simple average and the Kalman filter in [8,9,11] are competitors. In this paper, the accuracy means the closeness between the results of measurement and the true angular rate, which can be represented by the amount of measurements errors.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Compared with other models, the mean of virtual gyroscope combined by DCC model is reduced to 0.0047 °/s, so that the performance is also improved, and the improvement factor of the accuracy is about 5.17. simple average Kalman filter [8] Kalman filter [9] Kalman filter [11] dcc Figure 9. Allan variance results of the virtual gyro compared to the single gyro.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number N of component sensors in a gyroscope array can be selected as any integer, and from the results of [7,14], it demonstrated that the performance of a KF can be further improved through increasing number N of the component sensors. Additionally, the KF will show the best performance while the correlation factor ρ approaches −1/( N − 1), thus it will not need a large negative correlation factor to obtain the highest accuracy improvement by increasing the number N , which reduces the requirement of a negative correlation factor and is suitable for system implementation.…”
Section: Methodology Comparison Of the Virtual Gyroscope System Modelmentioning
confidence: 99%